Forward scattering radar for real-time detection of human activities and fall classification - Abdulhameed, Ali Ahmed (2019)
Falls pose a considerable threat that raises concerns among the elderly aged 65 and above worldwide. Many approaches have been used such as wearable and non- wearable sensors to observe their activities for mitigation of falling event consequences. However, these approaches have many constraints especially those related to false alarms, light sensitivity, occlusion, and personal privacy invasion. Radar technologies work independently of light, weather, and occlusion. They also provide advantages of a very low false alarm rate, and preserving personal privacy. The purpose of using radar is to detect, identify and recognize the moving targets based on the Doppler phenomenon generated from the interaction of the transmitting electromagnetic waves with the moving parts of the target. Two main types of radar technologies are available, the monostatic and bistatic radars. In bistatic radar, the bistatic angle plays a major role in measuring radar Doppler frequency. Forward scattering radar (FSR) is described as a special case of bistatic radar when the bistatic angle is near to 180°. The FSR system has some outstanding features compared to the conventional monostatic and bistatic radar including, enhancing radar cross-section of the target, relatively simple hardware, high ability to detect low observable targets regardless of the target’s shape and coating materials, and the absence of signal phase fluctuations.